STRATEGIC DIRECTIONS OF STATE SOCIAL POLICY IN WORKING WITH YOUNG FAMILIES - Khasan Imomnazarov (Bright Mind Publishing, 2025)
This article presents a scientific and theoretical analysis of the relevance of addressing the issues related to young families as one of the key priorities of modern social policy. Within the framework of the state's social policy, strategic measures aimed at improving the socio-economic conditions of young families, providing them with comprehensive support, ensuring employment, improving housing conditions, and guaranteeing equal access to education and healthcare are examined. The article also analyzes normative legal documents, social programs, benefits, and subsidies adopted by the state, as well as the role and significance of young families in strengthening their position in modern society. Based on academic sources, statistical data, and practical examples, the article identifies key factors for enhancing the effectiveness of the social protection system for young families.
Keywords: young families, social policy, state support, strategic directions, social protection, housing issues, employment policy, demographic policy, family well-being, social stability, state programs, social policy of Uzbekistan